ANALYSIS OF THE LEVEL OF KNOWLEDGE, SKILLS AND ATTITUDE OF FARMERS IN HANDLING SCABIES IN GOAT FARMING IN THE MAJENE DISTRICT - Suhartina, Suhartina; Khaliq, Taufik Dunialam; Said, Nur S.; Fahrodi, Deka U.; Sari, Nini N. (Universitas Nusa Cendana, 2024)
One disease that often occurs in goats is mange. Scabies is an ectoparasitic skin disease caused by Sarcoptes scabiei. This study aims to determine the level of knowledge, skills, and attitudes of breeders in handling scabies in goats in Majene Regency. The sampling method uses a non-probability sampling method, namely a sampling technique that does not provide equal opportunities for each element or member of the population to be selected as a sample. The sampling technique used was purposive sampling. The population in this study consisted of goat breeders in Tubo Sendana District and Banggae District, Majene Regency with a population of 583 breeders and a sample size of 85 people. The results of the study showed that the highest percentage of goat breeders' knowledge regarding scabies management was in the medium criteria, namely 55.3%, the highest percentage of breeders' skills was in the medium criteria, namely 50.6% and the highest percentage in the breeders' attitude category was in the medium criteria, namely 48.2%.